Application of the first approximation of the K-harmonics method to the 0+ states of 16O - Alcarás, J.A.Castilho; Da Silveira, H.Viana (Elsevier, 1978)
The energy levels of the 0+ states, the charge form factor and the rms charge raidus of 16O were calculated in the first approximation of the K-harmonics method. The results obtained for the ground-state energy, charge form factor and rms charge radius are in agreement with the experimental results, but this is not the case for the energies of the 0+ excited states. © 1978.